The wound healing and skin restoration properties of baeckea frutescens / Hasseri Halim - Halim, Hasseri (Faculty of Pharmacy, 2024)
Chronic wounds, particularly in aging populations and individuals with diabetes or obesity, pose significant healthcare challenges due to delayed healing and persistent inflammation. Among various approaches, plantbased remedies have emerged as a promising avenue. Baeckea frutescens, a shrub native to Southeast Asia, has shown potential as a wound-healing agent based on traditional use and scientific validation.